Genome sequence of a European Diplocarpon coronariae strain and in silico structure of the mating-type locus - Richter, Sophie; Kind, Sabine; Oberhänsli, Thomas; Schneider, Michael; Nenasheva, Natalia; Hoff, Katharina; Keilwagen, Jens; Yeon, Il-Kweon; Philion, Vincent; Moriya, Shigeki; Flachowsky, Henryk; Patocchi, Andrea; et al. (Frontiers in Plant Science, 2024)
Diplocarpon coronariae is a fungal pathogen that is prevalent in low-input apple production. Over the past 15 years, it has become increasingly distributed in Europe. However, comprehensive insights into its biology and pathogenicity remain limited. One particular aspect is the rarity of the sexual morph of this pathogen, a phenomenon hitherto unobserved in Europe. Diplocarpon coronariae reproduces through a heterothallic mating system requiring at least two different mating types for sexual reproduction. Genes determining the mating types are located on the mating-type locus. In this study, D. coronariae strain DC1_JKI from Dresden, Germany, was sequenced and used to unravel the structure of the mating type locus. Using short-read and long-read sequencing methods, the first gapless and near-complete telomere-to-telomere genome assembly of D. coronariae was achieved. The assembled genome spans 51.2 Mbp and comprises 21 chromosome-scale contigs of high completeness. The generated genome sequence was used to in silico elucidate the structure of the mating-type locus, identified as MAT1-2. Furthermore, an examination of MAT1-1 and MAT1-2 frequency across a diverse set of samples sourced from Europe and Asia revealed the exclusive presence of MAT1-2 in European samples, whereas both MAT loci were present in Asian counterparts. Our findings suggest an explanation for the absence of the sexual morph, potentially linked to the absence of the second mating idiomorph of D. coronariae in European apple orchards.